Sistem Perawatan pada Mesin Pembangkit/Genset pada PT. Menara Bosowa Menggunakan Metode Running test - Untung Saputra; Rahmat Aprian Arif; Safar Dune; La Ode Savirno (Program Pendidikan Vokasi Teknik Mesin, 2023)
Genset (generator set) is a device that functions to produce electrical power. Referred to as a generator set with the understanding that it is a set of combined equipment from two different devices, namely the engine and generator or alternator. Engine as a rotating device while the generator or alternator as a generating device. The development of the industrial world is so rapid, this increasingly advanced technology automatically encourages the rate of production to be even greater. The purpose of this work is to find out the work system on the generator engine/generator set, and determine the ability of the generator engine/generator set capacity. Observations were made from February 24, 2023 to April 6, 2023, at PT Menara BOSOWA, South Sulawesi. Data collection techniques using two data, namely primary and secondary data. The method in maintaining the generator engine at PT. Menara Bosowa uses the Runing Test method. Based on the observation, it shows that the generator set/genset engine produces different data every six weeks. It is recommended that PT Menara Bosowa continue to apply the running test method as part of the maintenance system on their generator set engine. This will help maintain optimal engine performance, prevent unnecessary damage, and extend the life of the generator set. In addition, it is important to follow the genset manufacturer's recommendations and perform regular preventive maintenance to maintain the reliability and efficiency of the power generation system at PT Menara BOSOWA.